A Cadaveric Study Assessing the Accuracy of Ultrasound‐Guided Sacroiliac Joint Injections. Issue 12 (10th May 2016) - Perry, Jason M.; Colberg, Ricardo E.; Dault, Stacey L.; Beason, David P.; Tresgallo, Ruben A.
Abstract: Background: Ultrasound guidance has been proposed as an alternative imaging modality for sacroiliac (SI) joint injections. Few studies have been published on the accuracy of this modality for the procedure. Objective: The objective of this study was to determine the accuracy of ultrasound‐guided SI joint injections using a cadaveric model. Design: Controlled laboratory study. Setting: The study was performed in the Skills Laboratory of the American Sports Medicine Institute in St. Vincent's Hospital, Birmingham, AL. Methods: Seventeen cadaveric SI joints were injected under ultrasound guidance and dissected to determine the accuracy of intra‐articular injections. Main Outcome Measurements: The presence of intra‐articular spread of a white paint marker in the SI joint after ultrasound‐guided injection. Results: Of 17 SI joints, 15 (88.2%) were accurately injected intra‐articularly. One of the joints with no intra‐articular spread was found to be partially frozen at the time of dissection, and the second joint was considered an unsuccessful injection before dissection due to difficulty entering the joint under ultrasound guidance because of marginal osteophytes at the joint line. Of the 15 joints with intra‐articular placement, 5 joints (33.3%) showed partial extra‐articular spread at the time of initial injection and required redirection of the needle under ultrasound guidance, and 3 joints (20%) had extra‐articular spread that was not seen during ultrasound. Conclusion: Ultrasound allowed intra‐articular injection in 88.2% of joints in this cadaveric study. Ultrasound does not expose the patient to radiation, as seen with fluoroscopic guidance, which is currently the gold standard for this injection. In addition, ultrasound may allow visualization of extra‐articular spread when caused by extra‐articular needle placement, which can allow for redirection of the needle to achieve intra‐articular injection. Level of Evidence: IV